2017
DOI: 10.1038/ncomms14733
|View full text |Cite
|
Sign up to set email alerts
|

Steviol glycosides enhance pancreatic beta-cell function and taste sensation by potentiation of TRPM5 channel activity

Abstract: Steviol glycosides (SGs), such as stevioside and rebaudioside A, are natural, non-caloric sweet-tasting organic molecules, present in extracts of the scrub plant Stevia rebaudiana, which are widely used as sweeteners in consumer foods and beverages. TRPM5 is a Ca2+-activated cation channel expressed in type II taste receptor cells and pancreatic β-cells. Here we show that stevioside, rebaudioside A and their aglycon steviol potentiate the activity of TRPM5. We find that SGs potentiate perception of bitter, swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 47 publications
4
124
1
1
Order By: Relevance
“…In addition, as our data showed that a TRPM5 inhibitor can alleviate behavioral bitter aversion in chickens, this suggests the possibility of modifying chickens' taste perceptions to feed ingredients by a TRPM5 activator such as steviol glycosides (Philippaert et al 2017) or an inhibitor. In addition, as our data showed that a TRPM5 inhibitor can alleviate behavioral bitter aversion in chickens, this suggests the possibility of modifying chickens' taste perceptions to feed ingredients by a TRPM5 activator such as steviol glycosides (Philippaert et al 2017) or an inhibitor.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, as our data showed that a TRPM5 inhibitor can alleviate behavioral bitter aversion in chickens, this suggests the possibility of modifying chickens' taste perceptions to feed ingredients by a TRPM5 activator such as steviol glycosides (Philippaert et al 2017) or an inhibitor. In addition, as our data showed that a TRPM5 inhibitor can alleviate behavioral bitter aversion in chickens, this suggests the possibility of modifying chickens' taste perceptions to feed ingredients by a TRPM5 activator such as steviol glycosides (Philippaert et al 2017) or an inhibitor.…”
Section: Resultsmentioning
confidence: 71%
“…We also observed that TRPM5 is involved in chickens' taste transduction, and this finding implies the possibility that chickens have thermal sensitivity of taste perception, and that the temperature of feeds affects taste perception of chickens. In addition, as our data showed that a TRPM5 inhibitor can alleviate behavioral bitter aversion in chickens, this suggests the possibility of modifying chickens' taste perceptions to feed ingredients by a TRPM5 activator such as steviol glycosides (Philippaert et al 2017) or an inhibitor. Figure 3 (A-C) The chicks' intakes of quinine hydrochloride (QHCl) solution were significantly decreased from 1.0 mmol/L compared to water, and their intakes of diphenidol hydrochloride (DHCl) solution were significantly decreased from 0.5 mmol/L.…”
Section: Resultsmentioning
confidence: 71%
“…TRPM5 is a Ca 2+ -dependent cation channel expressed in both type II taste receptor cells and pancreatic β-cells. 5 In the current study, we ex- histocompatibility (MHC) class I molecule has been found to be positively correlated with diabetes duration. 33 In addition, Pavlovic et al found elevated glucose levels to increase MHC class I mRNA levels twofold in both rat and human islet cell preparations, suggesting that a hyperglycaemic state is able to increase expression in islet β-cells.…”
Section: Effects Of 72-h Exposure To Svg On Gene Transcription In Mmentioning
confidence: 77%
“…Besides the sweet property, steviol glycosides also possess potential therapeutic benefits. A multitude of preclinical and clinical studies have demonstrated their antihyperglycaemic effects, including lowering postprandial blood glucose, 3,4 enhancing insulin secretion [5][6][7][8][9][10][11] and improving insulin sensitivity. 12,13 Steviol glycosides share steviol (ent-13-hydroxykaur-16-en-18oic acid) as the aglycone core structure and only differ in the number and type of sugar molecules attached (at R1 and R2), see Figure 1A Moreover, all steviol glycosides found in stevia leaf extracts share the same metabolic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one of the downstream signaling molecules of taste receptors, TRPM5, a Ca 2+ -activated cation channel, has been reported to localize in pancreatic β-cells. 40,41 Therefore, to elucidate the role of NNAT, it may be necessary to clarify the signaling pathways involved in keratinization in the filiform papillae of the tongue and the IRS in the hair follicle, in acrosome formation in the spermatozoa, in photoreception in the rod photoreceptors, and in characteristic signals in NNAT-positive stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 99%